Superficial corneal crosslinking during laser in situ keratomileusis. Issue 10 (October 2015) - Seiler, Theo G.; Fischinger, Isaak; Koller, Tobias; Derhartunian, Viktor; Seiler, Theo
Abstract : Purpose : To determine the safety of superficial corneal crosslinking after laser in situ keratomileusis (LASIK). Setting : Institut für Refraktive und Ophthalmo‐Chirurgie, Zurich, Switzerland. Design : Prospective study. Methods : Eyes with an ectasia risk score of 2 or higher were treated with standard LASIK (90 μm flap) for myopia correction, after which a rapid corneal crosslinking was performed in the interface (riboflavin 0.5% for 2 minutes, 9 mW/cm 2 for 5 minutes) (Group 1). The follow‐up was up to 1 year. The prevalence of complications was statistically compared with that in a group of eyes matched regarding age, sex, and attempted refractive correction that were treated with standard LASIK only (Group 2). Results : One month postoperatively, 5 eyes in Group 1 lost 1 line of corrected distance visual acuity (CDVA) compared with 1 eye in Group 2 ( P < .05). One year postoperatively, all eyes regained their preoperative CDVA, indicating a complication rate of less than 5%. The refractive success was identical in both groups. Early postoperative complications such as erosions (16%), diffuse lamellar keratitis (DLK) stage 1 (38%), and DLK stage 2 (5%) were statistically significantly more frequent after superficial corneal crosslinking, leading to a statistically significantly reduced uncorrected distance visual acuity at 1 month ( P < .001). Conclusions : Based on 1‐year results, superficial corneal crosslinking might be considered a safe adjunct to LASIK, with a delayed visual rehabilitation and a higher prevalence of transient side effects. It is not proved whether superficial corneal crosslinking can prevent iatrogenic keratectasia. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.